الذوق الجمالي في الثقافة الاسلامية - بن عثمان فهيمة (University of Eloued جامعة الوادي, 2024)
يظهر الاهتمام بالذوق الجمالي جليا في ثقافتنا الإسلامية ، سواء من خلال تتبعنا لما جاء في القرآن الكريم أو السنة النبوية الشريفة، فقد ارتبطت العبادات بالطهارة من خلال وجوب الغسل و الوضوء، و الطهارة ترمز للجمال و النظافة في البدن و الرائحة الطيبة التي تتحقق بفضلهما، و ارتبطت العبادات بنظافة و طهارة المكان و التحرز من كل نجس، و ارتبطت الصلاة بالمساجد التي يلبس المسلم لها أجمل الثياب ، وارتبط جمال المسلم بجمال روحه و تطهيرها من كل أمراض القلوب ، كما ارتبط المسلم في علاقاته بإخوانه بجميل الأخلاق ، و يحرص المسلم على البيئة النظيفة و الاعتناء بالطبيعة، و في الإسلام نهي عن الخيلاء في المشي و نهي عن رفع الأصوات و غيرها من مظاهر اهتمام الإسلام بوجود الذوق الجمالي في كل مجالات حياتنا ، و هذا البحث يسعى لإظهار هذا الاهتمام بجميل المظهر و السلوك و التفكير في الإنسان المسلم . Abstract: The interest in aesthetic taste appears clearly in our Islamic culture, whether by following what is stated in the Holy Qur’an or the Noble Prophet’s Sunnah. Worship has been linked to purity through the necessity of washing and ablution, and purity symbolizes beauty and cleanliness in the body and the pleasant smell that is achieved thanks to them. Worship was linked to the cleanliness and purity of the place and avoiding every impurity. Praying in mosques was linked to wearing the most beautiful clothes. The beauty of a Muslim was linked to the beauty of his soul and its cleansing of all diseases of the heart. The Muslim was also linked in his relationships with his brothers to beautiful morals, and he was keen on a clean environment and taking care of nature. In Islam, it is forbidden to show off when walking and to raise one’s voice. Other manifestations of Islam’s interest in the presence of aesthetic taste in all areas of our lives, and this research seeks to show this interest in the beautiful appearance, behavior and thinking of the Muslim person
Keywords: النظافة; الجمال; الذو; ق; جمال الر; الطبيعة; Taste; beauty; cleanliness; beauty of the soul; beauty of nature